Understanding and Mitigating Cyberfraud in Africa (2024) - Oluwatoyin E Akinbowale; Mariann P Mashigo; Mulatu F Zerihun (AOSIS Books, 2024)
The book covers the overview of cyberfraud and the associated global statistics. It demonstrates practicable techniques that financial institutions can employ to make effective decisions geared towards cyberfraud mitigation. Furthermore, the book contains some emerging technologies, such as information and communication technologies (ICT), forensic accounting, big data technologies, tools and analytics employed in fraud mitigation. In addition, it highlights the implementation of some techniques, such as the fuzzy analytical hierarchy process (FAHP) and system thinking approach, to address information and security challenges. The book combines a case study, empirical findings, a systematic literature review, and theoretical and conceptual concepts to provide practical solutions for mitigating cyberfraud. The major contributions of this book include the demonstration of digital and emerging techniques, such as forensic accounting for cyberfraud mitigation. It also provides in-depth statistics about cyberfraud, its causes, its threat actors, practicable mitigation solutions, and the application of a theoretical framework for fraud profiling and mitigation.